Investigation of Bacterial Persistence and Filaments Formation in Clinical Klebsiella pneumoniae: First Report from Iraq - Aziz, Sarah N.; Al Marjani, Mohammed F. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2022)
Bacterial persistence is recognized as a major cause of antibiotic therapy failure, causing biofilms, and chronic intractable infections. The emergence of persisters in Klebsiella pneumoniae isolates has become a worldwide public health concern. The goal of the present study is to investigate the formation of persister cells beside filaments in Iraqi K. pneumoniae isolates. A total of fifty clinical K. pneumoniae isolates were collected from different clinical specimens and identified using the genotypic identification by using specific primer (rpoB gene) from housekeeping genes. Persister cells investigation is performed by exposure of stationary phase K. pneumoniae isolates to a high concentration of ciprofloxacin (×10 MIC) and counting the number of viable persister cells by CFU counts. Bacterial filament formation is detected and measured by light microscope scanning electron microscope. The results show the bility of these pathogenic bacteria to form persister cells to survive the bactericidal antibiotics and to cause chronic infection.Furthermore, persistent isolates have the ability to change in shape and size extensively, about 4 times increase in cell length than their normal length. These phenomena are possibly the initial stages of bacterial resistance prevalence.